2021
DOI: 10.1016/j.mex.2021.101213
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical modeling approach for thermomechanical low cycle fatigue analysis of cyclically non-stabilized steels

Abstract: The widely used fatigue life prediction models, such as the Coffin–Manson model or S–N curve related models are based on the assumption that the response of a material experiencing low cycle fatigue loading is stabilized during some period. However, for many materials such a stabilized state is hardly observed, and the activated mechanisms for cyclic hardening or softening depend on test conditions. In general, the selected test conditions (stress or strain control) should depend on the intended use of the obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…On the other hand, under the conditions of (strain-controlled tests with total strain amplitude ), cyclic creep does not occur. For this reason, strain-controlled tests are preferable, because the existence of creep during stress-controlled tests hinders the analysis of test results [ 19 ]. Based on the research described in the literature [ 5 , 6 ], it can be concluded that changes in loop plastic strain under the conditions of are much larger than changes in this parameter under .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, under the conditions of (strain-controlled tests with total strain amplitude ), cyclic creep does not occur. For this reason, strain-controlled tests are preferable, because the existence of creep during stress-controlled tests hinders the analysis of test results [ 19 ]. Based on the research described in the literature [ 5 , 6 ], it can be concluded that changes in loop plastic strain under the conditions of are much larger than changes in this parameter under .…”
Section: Resultsmentioning
confidence: 99%
“…In [ 16 ] the above formula was used as the basic relation for summing the fatigue damage in terms of the plastic strain energy, while in papers [ 18 , 19 ]—for the analysis of the low-cycle fatigue tests results obtained under various load conditions. The energy-based description can also be used when analyzing the results of tests performed under the conditions of load programs including a sequence of constant (creep) and variable (fatigue) loads.…”
Section: Methodsmentioning
confidence: 99%